Antioxidants reduce TGF-beta2-induced gene expressions in human optic nerve head astrocytes - Yu, Alice L.; Welge-Lüssen, Ulrich-Christoph (Acta Ophthalmologica, 2013)
The goal of the present study was to investigate whether the antioxidants vitamin E, vitamin C and vitamin B1 can reduce the transforming growth factor-beta2 (TGF-?2)-induced gene expressions in cultured human optic nerve head (ONH) astrocytes.Cultured human ONH astrocytes were pretreated with different concentrations of vitamin E, vitamin C and vitamin B1 and then exposed to 1.0 ng/ml TGF-?2 for 24 hr. Expression of the heat shock proteins Hsp27 and ?B-crystallin, the extracellular matrix (ECM) component fibronectin and the ECM-modulating protein connective tissue growth factor (CTGF) was detected by immunohistochemistry or real-time PCR analysis.TGF-?2 increased the expression of Hsp27, ?B-crystallin, fibronectin and CTGF in human ONH astrocytes. Pretreatment with different concentrations of vitamin E, vitamin C and vitamin B1 reduced the TGF-?2-stimulated gene expressions.In cultured human ONH astrocytes, the TGF-?2-stimulated gene expressions could be reduced by pretreatment with vitamin E, vitamin C and vitamin B1. Therefore, the use of antioxidants in glaucomatous optic neuropathy might be a promising approach to prevent TGF-?2-induced cellular changes in ONH astrocytes.
EVALuna2:21127